100 snowflakes to crochet make your own snowdrift-- to give or to keep - Sainio, Caitlin (London Search Press, 2012)
"Bring the magic of a fresh snowfall into your own home with this gorgeous collection of crocheted snowflakes. Spend an hour making an ornament or two, or take a weekend and crochet a whole blizzard" --P. [4] of cover
The basics. Tools and materials ; Patterns and abbreviations ; Crochet refresher course -- Snowflake showcase -- Snowflake patterns. Beginner patterns ; Intermediate patterns ; Advanced patterns -- Projects
Includes index
1
Keywords: Crocheting -- Patterns; Snowflakes in art